Derivatives Effect on Monetary Policy Transmission - Vrolijk, Coenraad (IMF Working Papers; Working Paper, 1997)
This paper examines changes in the monetary policy transmission mechanism in the presence of derivatives markets. The effect of adding derivatives markets is analyzed independently for each of the main channels of monetary policy transmission: interest rates, credit, and exchange rates. Theoretically, derivatives trading speeds up transmission to financial asset prices, but changes in the transmission to the real economy are ambiguous. Using the structural vector autoregression methodology, an empirical study of the United Kingdom is used to assess the impulse responses of output and inflation, controlling for the size of the U.K. derivative markets. No definitive empirical support for a change in the transmission process is found.